PCF11, a Novel CD44-Downstream Transcriptional Target, Linking Its 3’-End Polyadenylation Function to Tumor Cell Metastasis - Al-Mansoob, Maryam; Ahmad, Salma M. S.; Ouhtit, Allal (Frontiers in Oncology, 2022)
Breast Cancer (BC) is the most common and the major health issue in female women worldwide. Metastasis, a multistep process, is the worst aspect of cancer where and tumor cell invasion is the defining step. Tumor cell invasion requires cell adhesion molecules (CAMs), and alterations in CAMs is considered as an initiating event in metastasis. Among CAMs, CD44 is a large family of more than 100 isoform, and its precise function was initially controversial in BC. Therefore, awe have previously established a (Tet)-off inducible expression system of CD44 in MCF-7 primary BC cell line, and showed that CD44 promoted BC invasion/metastasis both in vitro and in vivo. A microarray gene expression profiling revealed more than 200 CD44-downstream potential transcriptional target genes, mediating its role in BC cell invasion and metastasis. Among these CD44-target genes, the Pre-mRNA cleavage complex 2 protein (PCF11) was upregulated upon the activation of CD44 by its major ligand hyaluronan (HA); This, prompted us to hypothesize PCF11 as a potential novel player in the transcriptional target of CD44-downstream signaling that promoted BC cell invasion and metastasis. A large body of evidence from the literature supports our hypothesis that CD44 might regulate PCF11 via MAPK/ERK pathway. This review aims to discuss these findings from the literature that support our hypothesis, and further provide possible mechanisms linking CD44-promoted cell invasion through regulation of its potential target PCF11.